THEORETICAL-PEDAGOGICAL FOUNDATIONS OF INFORMATION-COMMUNICATIVE COMPETENCE DEVELOPMENT IN FUTURE ENGLISH LANGUAGE TEACHERS - Pulatova, Khilola (Журнал иностранных языков и лингвистики, 2022)
Development of professional competence of future teachers one of the current issues. It will be discussed in the educational institutions of our Republic the communicative competence of the pedagogue is his team of students, parents, colleagues normative bases of implementation of effective mechanisms of communication with created.